Estrategias metodológicas en lecto-escritura y su incidencia en el proceso de enseñanza- aprendizaje de los estudiantes de 3er año de EGB de la UE Emigdio Esparza Moreno, Babahoyo.2022 - Espinoza Aguirre, Carmen Georgina (2022)
Reading-writing plays an important role in early childhood education; because it allows the development of the productive capacities of infants, generates an efficient basic motor coordination, developing and achieving different types of skills. The objective of the present investigation is to determine the incidence of the methodological strategies in reading-writing in the teaching-learning process of the 3rd year EGB students of the EU Emigdio Esparza Moreno, Babahoyo, period 2022. The methodology implemented in the The research has a descriptive correlational design by virtue of the fact that the case study has the purpose of describing each of the identified findings that allow the variables to be correlated. The types of research were applied and bibliographic. The population was made up of students and teachers belonging to the 3rd year of EGB of the EU Emigdio Esparza Moreno; whose sample was 35 students and 2 teachers. In addition, the techniques applied were direct observation of students and teachers; the instruments used were an observation sheet and a questionnaire of questions that allowed obtaining relevant information on the problem studied. The results of the research revealed that the methodological strategies of reading and writing implemented by the teachers are not very efficient; reason why, the teaching-learning process is not of quality and the students have poor reading and writing skills. In addition, the infants feel unmotivated because the activities carried out by the teachers are not very motivating, which negatively affects the learning of the infants.